Using appreciative inquiry to develop a research capacity development programme - Frantz, JM; Rhoda, AJ; de Jongh, J (South African Journal of Higher Education, 2016)
With academics struggling to find the balance between research and teaching, there is a need to identify strategies that would assist academics in making the necessary changes to manage their time. Appreciative inquiry is a strength-based change process based on the premise that academics are change agents who possess knowledge and experience that can make a difference. This article proposes an appreciative inquiry methodological framework for an academic development strategy focussing on integrating research into teaching. Currently few measures exist that focus on assisting academics in incorporating research into teaching and learning. The article aims to describe the strategies used to initiate a process that builds on the positive experiences of academics in teaching in an environment where academics may become overwhelmed when focussing only on barriers. The process described focuses on the aims of the academic development programme at each stage as well as the roles of the participants. The Appreciative Inquiry approach is a novel framework that can be used to initiate research capacity building among academics.